Chicken Swarm Optimization for Detecting Weed using Machine Learning Approach - E.Gangadevi, Dr. R. Shoba Rani, Dr. G. Victo Sudha George, D. Suganthi, P.Thamizhikkavi (International Journal of Advanced Science and Technology, 2020)
Food is the main source for human beings. There are lots and lots of issues which totally disturbs the field of Agriculture. The main annoyance found here are plant diseases, unhealthy soil, changing temperature and humidity, to use right fertilizers, water level, growth of weeds etc. This proposed method aims to answer the problem of farmers to identify the weeds from the crop field. Identifying weed and destroying it at right time will save the yield of the field. Since, weed may take the energy of the soil, a fertilizer which leads to unhealthy productivity of the actual plants. This is identified by using Machine Learning approach which shots the image of all parts of the field and compares the picture with the given dataset to detect weeds by applying Chicken Swarm Optimization Algorithm (CSO).